Assessment of Landing Gear Design Based on the Virtual Testing and Evaluation Methodology. (2015) - Hailiang, Liu; Lixin, Wang
Abstract: In order to provide rapid assessment of ground handling characteristics of a new type transport aircraft during the late preliminary design phrase, a nonlinear aircraft ground motion model was established. Integrated with pilot model, the simulation code is capable of predicting the responses of the aircraft while performing typical ground operation task, such as take-off, landing, taxiing, turning, and braking. Simulation results of aircraft typical ground operation are presented and analyzed with specific operational and handling criteria.